1996
DOI: 10.1128/aem.62.10.3572-3580.1996
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed-field gel electrophoresis and ribotype profiles of clinical and environmental Vibrio vulnificus isolates

Abstract: Vibrio vulnificus belongs to the autochthonous bacterial flora of warm estuarine waters. It can cause lifethreatening extraintestinal disease in persons who have underlying illness and who consume raw shellfish or contact wounds with estuarine water. Currently, very little is known about genetic diversity within this species. In this report, we describe high-level variation in restriction fragment length polymorphism profiles among 53 clinical and 78 environmental isolates, as determined by pulsed-field gel el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(34 citation statements)
references
References 45 publications
5
29
0
Order By: Relevance
“…Examination of the DNA ¢ngerprints from the clinical isolates used in this study (all of which caused fatality after consumption of raw oysters) using gel analysis and cluster analysis, revealed signi¢cant genetic diversity among these strains known to be fatal in susceptible human individuals. This result is consistent with data from several other studies (Aznar et al 1993;Buchrieser et al 1995;Tamplin et al 1996;Vickery et al 1996Vickery et al , 1998 which demonstrated that V. vulni¢cus strains isolated from environmental samples had a diverse genomic organization. To the best of our knowledge, this is the ¢rst study to examine AP-PCR DNA ¢ngerprints produced only from strains of V. vulni¢cus con¢rmed to be virulent in humans.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Examination of the DNA ¢ngerprints from the clinical isolates used in this study (all of which caused fatality after consumption of raw oysters) using gel analysis and cluster analysis, revealed signi¢cant genetic diversity among these strains known to be fatal in susceptible human individuals. This result is consistent with data from several other studies (Aznar et al 1993;Buchrieser et al 1995;Tamplin et al 1996;Vickery et al 1996Vickery et al , 1998 which demonstrated that V. vulni¢cus strains isolated from environmental samples had a diverse genomic organization. To the best of our knowledge, this is the ¢rst study to examine AP-PCR DNA ¢ngerprints produced only from strains of V. vulni¢cus con¢rmed to be virulent in humans.…”
Section: Discussionsupporting
confidence: 93%
“…vulni¢cus ¢ngerprints, the scored molecular weight data were exported to the statistical analysis program NTSYS-pc2 (Exeter Software, Setaukey, NY, USA) in a binary matrix format. The data were formatted so that the presence or absence of bands of speci¢c molecular weights was indicated either as a 0 (absence) or a1 (presence) (Go et al 1995;Tamplin et al 1996).The matrix was analysed ¢rst using the SIMQUAL algorithm of NTSYS-pc, which generated a similarity matrix for the data, comparing individual ¢ngerprints and assigning them similarity values. Cluster analysis was then performed on the similarity matrix data using the SAHN CLUSTERING (sequential, agglomerative, hierarchical and nested clustering), UPGMA (unweighted pairgroup method, arithmetic average) method algorithm in order to group the ¢ngerprints according to their similarity.…”
Section: Cluster Analysis Of Ap-pcr Generated Dna Fingerprintsmentioning
confidence: 99%
See 1 more Smart Citation
“…We studied two clinical isolates of V. vulnificus (LL728, and M06-24/O) obtained from patients who died of sepsis following ingestion of contaminated oysters and two environmental V. vulnificus strains isolated from seawater (MLT365 and MLT367) (Wright et al, 1990;Tamplin et al, 1996;Jackson et al, 1997;Starks et al, 2000). These clinical and environmental strains were selected from a collection based on their relative virulence and attenuation respectively (Wright et al, 1990;Starks et al, 2000).…”
Section: Bacterial Strains and Mediamentioning
confidence: 99%
“…Vibrio vulnificus is an autochthonous inhabitant of estuarine environments that is found at high population densities and diversities in oysters (Buchrieser et al, 1995;Tamplin et al, 1996;Jackson et al, 1997). This opportunistic pathogen is the leading cause of reported deaths associated with shellfish consumption (Hlady et al, 1993;DePaola et al, 2003), and it caused approximately 14.5% of the Vibrio infections reported by Foodborne Diseases Active Surveillance Network.…”
Section: Introductionmentioning
confidence: 99%